Pharmacokinetics of ceftazidime in normal and uremic subjects. - Leroy, A (1984)
The pharmacokinetics of ceftazidime, administered as a single intravenous dose of 15 mg/kg given in a bolus injection over 3 min, were investigated in 5 normal subjects and in 19 uremic patients. The subjects studied were divided into five groups according to values for endogenous creatinine clearance (CLCR): group I, five subjects with CLCR greater than 80 ml/min; group II, five patients with CLCR = 30 to 80 ml/min; group III, six patients with CLCR = 10 to 30 ml/min; group IV, four patients with CLCR = 2 to 10 ml/min; and group V, four anuric patients on hemodialysis. A two-compartment open model was used to calculate the pharmacokinetic parameters. In normal subjects, the mean apparent elimination half-life was 1.57 +/- 0.13 h. The central distribution volume and the apparent volume of distribution were 0.127 +/- 0.023 and 0.230 +/- 0.015 liter/kg, respectively. Of the injected dose, 83.6 +/- 3.6% was eliminated in the urine as parent drug within 24 h. The terminal half-life increased with impairment of renal function to about 25 h in severely uremic patients. Impairment of function did not significantly modify the half-life at alpha phase, central distribution volume, or apparent distribution volume. A 6- to 8-h hemodialysis procedure reduced concentrations of ceftazidime in plasma by approximately 88%, and the elimination half-life was 2.8 +/- 0.2 h. There was no evidence of accumulation of ceftazidime in four patients with severe and chronic impairment of function who received doses of 0.5 to 1.0 g every 24 h for 10 days.